1990
DOI: 10.1136/jmg.27.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Yunis-Varon syndrome with severe osteodysplasty.

Abstract: We report two male sibs and two female sibs from separate families, both with normal parents, who had a lethal condition with features of the YunisVaron syndrome and radiological signs of severe osteodysplasty. Autosomal recessive inheritance is likely in both families. The additional features described represent further delineation of the phenotype of the Yunis-Varon syndrome.The Yunis-Varon syndrome was recently reviewed by Hennekam and Vermeulen-Meiners' who added a further case to the seven reported previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…[2][3][4][5] hypoplastic scapulae, a mild kyphosis at the cervicothoracic junction, broad sacrosciatic notches, failure of ossification of the pubic bones and of the symphysis pubis, and left hip dislocation. The distal phalanx of the thumb, index, and little fingers were hypoplastic, the first metacarpal was short, and there was hypoplasia of the middle phalanges of both little fingers with clinodactyly.…”
mentioning
confidence: 99%
“…[2][3][4][5] hypoplastic scapulae, a mild kyphosis at the cervicothoracic junction, broad sacrosciatic notches, failure of ossification of the pubic bones and of the symphysis pubis, and left hip dislocation. The distal phalanx of the thumb, index, and little fingers were hypoplastic, the first metacarpal was short, and there was hypoplasia of the middle phalanges of both little fingers with clinodactyly.…”
mentioning
confidence: 99%
“…Several authors have reported patients with this condition; five cases, Garrett et al [1990] four cases, Hughes and Partington [1983] and Lapeer and Fransman [1992] reported the same case, and Partington [1988], Pfeiffer et al [1988], Hennekam and VermeulenMeiners [1989], Adès et al [1993], Dworzak et al [1995], Rabe et al [1996], Christie et al [1999], Walch et al [2000], Sumi et al [2004], Bhatia and Holla [2005], Kulkarni et al [2006] reported one case each. We also included unpublished clinical data on the sib of the patient described by Hennekam and VermeulenMeiners [1989].…”
Section: Methodsmentioning
confidence: 74%
“…In addition, fetal US for detection of polyhydramnion, hydrops fetalis, ventriculomegaly and additional brain abnormalities is of importance. Garrett et al [1990] a Limb X-ray results not reported in two patients.…”
Section: Clinical Recommendationsmentioning
confidence: 92%
“…Some patients reported as Yunis-Varon syndrome may have a distinct condition that resembles osteocraniostenosis. Garrett et al [1990] described a severe form of the Yunis-Varon syndrome in a patient with normal clavicles, supra-acetabular constrictions, and flared metaphyses. Patients 880 and 881 in REAMS [Hall and Washbrook, 2000] show extreme thinning of the long bones, fractures, drumstick-shaped metacarpals and phalanges (as in osteocraniostenosis), normal spine, and 1st ray hypoplasia.…”
Section: Discussionmentioning
confidence: 99%